The Effects of Financial Crises on Tourism in the Greater Mekong Sub-region: Panel ARDL Approach - NONTHAPOT, Sakkarin; SRICHAIYO, Porowes (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).14, 2017)
This study aims to investigate the effects of financial crises on tourism revenue in the Greater Mekong Sub-region (GMS) for five countries (Cambodia Thailand Myanmar, Laos, and Vietnam). The financial crises include the 2003 financial crisis (the Federal Reserve reducing the savings interest rate), and the 2008 financial crisis (the insolvency proceedings of the Lehman Brothers). The panel dataset over the period of 1995-2015 is estimated using the Panel ARDL model with the Pool Mean Group (PMG) approach. The study indicates that the financial crises in 2003 and 2008 decreased tourism revenue in the long-run. Therefore, each GMS country should have tourism policies to handle financial crises, and preventive measures to handle financial crises should be implemented in each country.